Ekologi dalam Nuansa Pondok Pesantren Sufistik - Fiqhi Fajriyah; Indah Rahmawati Oktavia Macdalena; Muhamad Afif (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2026)
The crisis of human spirituality, which separates the inner dimension from the universe, is at the root of the current global environmental crisis. The purpose of this study is to comprehensively examine how Sufi principles are applied in environmental conservation practices at the Shadana Islamic Boarding School in Padarincang, and to determine how the teachings of the book Fathul 'Arifin influence the formation of the students’ ecological ethics. This research was conducted qualitatively through a case study. Data were collected through document analysis, in-depth interviews, and participatory observation from September 22 to October 5, 2025. The results indicate that the concept of spiritual purification, or tazkiyatun nafs, is integrated with nature conservation by activating the seven lathaif. Environmental conservation, such as protecting springs and forests, is viewed as a form of spiritual devotion to the Creator, as human awareness of the elements of fire, water, wind, and earth fosters a strong inner connection with the macrocosm or the universe. The results indicate that the santri paradigm has shifted from anthropocentrism to theocentrism. This study proposes an “Eco-Sufism” model, grounded in the transformation of inner consciousness, as an alternative solution to address environmental degradation. This approach emphasizes that to foster sustainable harmony among humans, God, and the universe, ecosystem sustainability requires a strong foundation of spirituality.